Fishbone Analysis of Human Error and Risk Control in High-Risk Construction Projects (Case Study: Biodiesel Project, South Kalimantan) - Dwi Iin Novianti; Shine Pintor Siolemba Patiro; Rini Yayuk Priyati (Publikasi Indonesia, 2025)
Workplace accidents continue to be a significant concern in the construction industry, particularly in high-risk activities such as working at height. This study aims to identify hazards and analyze the root causes of human error using the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) and Fishbone Analysis approaches. The research uses a qualitative descriptive method, incorporating interviews, project photo/video observations, and document analysis to gather data. The findings reveal that the main contributing factors to human error include environmental conditions, human behavior, and work methods. Based on these findings, recommendations focus on enhancing supervision, implementing continuous safety training programs, ensuring the availability of ergonomic Personal Protective Equipment (PPE), and developing simple and effective work procedures. Fishbone Analysis proved to be an effective tool for identifying root causes and assisting in the development of a structured risk control strategy. The implications of this research emphasize the importance of a holistic approach to risk management, incorporating both technical and human factors to improve safety standards in construction projects.